Formação de professoras alfabetizadoras em uma perspectiva sociointeracionista: a (re)elaboração de conceitos e práticas docentes - Barreto, Maria do Socorro (2010)
Despite the investments in pre-service and in-service education for teachers, the rates in the official evaluations that indicate problems regarding the quality of the basic education in the Brazilian public schools – above all in the Northern and the Northeastern regions of the country – especially on the first years of schooling. These problems come up due to a number of factors, some of them regard the education of the teachers. Research on teachers´ schooling, on the other hand, are very useful, because they bring real contributions to the debate and to redefinitions of the concepts under this topic. Within this context, we insert this investigation on the education of literacy teachers. The starting question is: how can an interventionist research based on a sociointeractionist perspective contribute to the teachers‟ preparation, with the goal to elaborate/reelaborate the knowledge and practices in literacy process? With this paper, we aim specifically at characterizing and analyzing the movements and dynamics that compose an interventionist research that was, at the same time, an in- service experience focused on the teaching and learning of the written language; identifying how the interactions take place within the pairs (teacher-teacher) and what pieces of knowledge are constituted in this space, enabling action on the zone of proximal development of the teachers, and comprehending how the intervention of the researcher can foster the development on the learning of theories and the relationship between them and the literacy practice. The theoretical foundation was constituted by the contributions of the sociointeractionist theory, especially by the ideas defended by Vygotsky about mediation; zone of proximal development, intervention, here understood as the action taken by the researcher along with the teachers; and interaction, understood as the relationship among the colleagues. The psychogenesis of the written language, according to Ferreiro and Teberosky (1998), based the theory of literacy, besides the studies on pieces of knowledge and teachers‟ education, produced by authors, such as Nóvoa (1997), Sacritán (2002), Tardif (2002), Morais (2005), Leal (2005), among others. The qualitative approach was utilized along with the interventionist research. Practices, video recordings, questionnaires and interviews were observed and study groups were developed, these served not only as investigational space, but also as teachers‟ educational space. Five literacy teachers, all women, who worked in public schools in the city of Mossoró, Rio Grande do Norte, took part in the research. The findings point to the following conclusion: by promoting reflection regarding the pieces of knowledge and the practices of literacy teachers, taking them as the starting point, the interventionist research could contribute to the elaboration and reelaboration of teaching conceptions and practices. For this purpose, zones of actual development regarding knowledge and teaching practices were analyzed, as the basis for the researcher to intervene with the zones of proximal development. The singularity of the context in which the teachers are inserted was also considered as a resource in order to instigate them to reflect upon their knowledge and practices, so that they would aim at overcoming the difficulties they face at work, widening and varying their actions. The practices that took place with the students were also highlighted as indispensable elements for the intervention on the teachers‟ education process, bringing together, in a more effective way, theory and practice, an aspect that is highly demanded by the teachers. These findings point towards relevant issues that can subside future educationalpolicies and programs destined to the education of literacy teachers.